GPI-anchored complement regulatory proteins in seminal plasma. An analysis of their physical condition and the mechanisms of their binding to exogenous cells - Rooney, I A; Heuser, J E; Atkinson, J P (The Journal of clinical investigation, 1996)
We analyzed and compared the properties of three glycosylphosphatidylinositol (GPI)-anchored proteins. CD59, CD55 (both C regulators), and CDw52, and of the transmembrane C regulator CD46 in seminal plasma (SP). We demonstrated previously that anchor-intact SP CD59 is present on the membranes of vesicles (prostasomes) and that cells acquire this protein during incubation with SP. We now report that this acquisition is due partly to adherence of prostasomes to cells and partly to a second mechanism which may involve micellar intermediates. Using fluorescent labeling, ultracentrifugation, and density gradient centrifugation, virtually all CD46 was present on prostasomes whereas CD59, CD55, AND CDw52 were also detected in a form which remained in the 200,000 g supernatant and equilibrated at higher density than prostasomes in gradients. All three GPI-linked proteins eluted at high molecular mass during size exclusion chromatography of this nonprostasome fraction. As documented by videomicroscopy and biochemical analysis, cells acquired new copies of the GPI-linked proteins during incubation with the nonprostasome fraction as well as with prostasomes. These data demonstrate the presence in SP of a stable population of membrane-free, GPI-linked proteins available for transfer to cells. Binding of these proteins to spermatozoa and pathogens in SP may confer new properties on their membranes including increased resistance to C attack. Finally, our data raise the possibility that lipid-associated GPI-linked proteins may be suitable for therapeutic applications.